(untitled) (Iraqi Journal of Medical Sciences, 2017)
Quality in healthcare is imperative and not optional. To deliver continuous process improvement, the focus must be on the patient from start to finish, as often the patient’s experience of receiving care is the product of the process as in doctor consultation setting. Value healthcare can be formulated as an equation: quality divided by cost. Sometimes to do less is to achieve more, as beyond the point of optimal healthcare, adverse effects will outweigh perceived benefits. Patient safety is proportional to process quality; hence the overarching importance of focusing on quality. However, costs must always be harnessed to ensure we achieve optimality of healthcare delivery. Keywords :Change management, errors, events reporting, frontline staff, harm events, healthcare delivery, information flow, leadership, near misses, patient safety, quality care, risk management, process improvement, system data. Citation: Alani A. Delivering Quality Care and Patient Safety – A New Paradigm. Iraqi JMS. 2017; Vol. 15(3): 214-219. doi: 10.22578/IJMS.15.3.1